Zinc lozenges efficacy in cold treatment - Dobrzyński, Michał; Czarnota, Jakub; Sokół, Dorota; Skubel, Tomasz; Standyło, Arkadiusz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2019)
Introduction: Until now zinc has been used mainly in oral pellets form when it was an insufficiency of this element in the body. Zinc as a lozenge or used locally on the skin found use in dermatology, ophthalmology and removing halithosis. Recently scientific publications suggesting that zinc lozenges can shorten the duration of cold even 30% appeared. The aim of the study is to analyze available scientific data considering zinc lozenges efficacy in cold treatment. Material and method: The study uses research results published on the PubMed platform. Results: Comparative diagrams were made in order to clearly depict effectiveness of certain zinc doses and forms on shortening the duration of cold. The most important is dose and type of zinc compound. Zinc acetate and gluconate show the best therapeutical activity applied in dose >75mg per day. Conclusions: According to the most of included research taking zinc lozenges reduces the duration of illness. Moreover the industrial process of making pellets is significant. Commonly used additional ingredients can bind zinc ions preventing their local activity In oral cavity. Properly prepared drug can be very effective way of shortening the duration of cold.